Accessory cell and HLA compatibility requirements for the generation of specific in-vitro antibody responses to influenza virus by human blood lymphocytes. - Mitchell, D; Beverley, P; Boyle, D; Winger, L; Callard, R (1983)
The role of antigen presenting cells in specific in-vitro antibody responses to influenza virus by human lymphocytes was investigated. Demonstration of a requirement for accessory cells necessitated vigorous depletion procedures. Accessory cells were removed by passage of mononuclear cells through a Sephadex G10 column followed by separation of cells bearing antigens defined by the monoclonal antibodies OKM1 and UCHM1 by fluorescence-activated cell sorting or panning. Peripheral blood mononuclear cells treated in this way were unable to respond to influenza virus by antibody production in either round-bottom or flat-bottom culture wells. The response could be reconstituted by either irradiated plastic-adherent cells or G10 non-adherent OKM1/UCHM1 positive cells in both autologous or allogeneic (HLA-DR different) combinations. The absence of HLA restriction was not due to non-specific allogeneic effects and was confirmed using irradiated, antigen-pulsed accessory cells which were extensively washed, incubated overnight and washed again to remove free antigen. These data suggest that the normal T-cell repertoire contains T helper cells specific for antigen plus self and antigen plus allo MHC.